THE INFLUENCE OF COOPERATIVE THINK PAIR SHARE LEARNING MODEL AND LEARNING INTEREST ON LEARNING OUTCOMES OF CLASS IV STUDENT PPKN AT SD NEGERI 118444 PODO RUKUN - Nina Agustina Ritonga; Daulat Saragi; Yusnadi Yusnadi (Sensei International Journal of Education and Linguistic, 2021)
This study aims to analyze: (1) the influence of the cooperative learning model is higher than the conventional learning model; (2) the learning outcomes of students who have high learning interest are higher than students who have low learning interest (3) the interaction between cooperative learning models and student learning interest influences student learning outcomes. The research was in the form of a Quasi Experimental Design with a 2x2 factorial. The instruments used were the PPKn learning outcomes test and the Learning Interest instrument. Data analysis used two-way ANOVA. The results showed: (1) There is an effect of the cooperative learning model on student PPKn learning outcomes in class IV SD Negeri 118444 Podo Rukun; (2) The learning outcomes of students who have high learning interest are higher than students who have low learning interest; (3) There is an interaction between the Cooperative learning model and learning interest on the learning outcomes of Student PPKn at SD Negeri 118444 Podo Rukun.